REORIENTATION OF INOVATION IN ISLAMIC EDUCATION EVALUATION DURING PANDEMIC - Hasanah, Uswatun; Fadilah, Nurul (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2021)
Evaluation in Islamic Education during the Covid-19 Pandemic needs to be modified from its’ systems, approaches, and procedures according to the needs, situations and conditions. This study examines the dynamics in the innovation of Islamic learning evaluation, which is carried out using a descriptive approach in the form of a literature study. The content analysis was used in analyzing various sources data from previous studies and discussions on the reseach topic. The result reveals that there are several innovative models of Islamic education evaluations that were modified as alternatives during the Covid-19 pandemic, such as online-based evaluations on the cognitive aspects carried out with several forms of evaluation, namely questions in the form of multiple choice tests, questions in the form of essay tests, portfolios, and oral exams which are adapted to different online platforms and technical guidelines. In the affective and spiritual aspects, several forms of evaluation used are projective assessment, objective assessment, attitude and spiritual assessment rubrics. Meanwhile, the psychomotor aspect is carried out using a skills assessment rubric. All types of assessment are modified and adjusted in the application system, and the system for providing evaluation reports of  cognitive, affective, and psychomotor which are submitted online to get a description of the progress experienced by students.